2021
DOI: 10.1097/aud.0000000000001082
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the Auditory System in Children With Hypothyroidism: A Systematic Review and Meta-Analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Alternative rationales may exist for these findings, including variables unknown or not evaluated. For example, metabolic and endocrine disorders such as hypothyroidism [ 46 , 47 , 48 , 49 ], diabetes [ 50 , 51 ], and polycystic ovarian syndrome (PCOS) [ 52 , 53 ] have been associated with both hearing loss and alterations in vitamin A nutritional status. Subclinical hypothyroidism is particularly common during pregnancy, affecting an estimated 15.5% of pregnant women in the United States [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative rationales may exist for these findings, including variables unknown or not evaluated. For example, metabolic and endocrine disorders such as hypothyroidism [ 46 , 47 , 48 , 49 ], diabetes [ 50 , 51 ], and polycystic ovarian syndrome (PCOS) [ 52 , 53 ] have been associated with both hearing loss and alterations in vitamin A nutritional status. Subclinical hypothyroidism is particularly common during pregnancy, affecting an estimated 15.5% of pregnant women in the United States [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hypothyroidism is associated with increased concentrations of β-carotene [ 46 , 47 ]. Maternal hypothyroidism and congenital hypothyroidism are also linked to neurosensory hearing loss [ 48 , 49 ], although less is known about how subclinical hypothyroidism may affect infant hearing. One study by Radetti et al failed to detected any significant association between maternal subclinical hypothyroidism and infant hearing outcomes [ 55 ], while a study by G et al observed that infants born to mothers with subclinical hypothyroidism had minor alterations in hearing which self-corrected within 6–8 months [ 56 ].…”
Section: Discussionmentioning
confidence: 99%